Efficacy of Multi-Modal Migraine Prophylaxis Therapy on Hyperacusis Patients. (May 2020) - Abouzari, Mehdi; Tan, Donald; Sarna, Brooke; Ghavami, Yaser; Goshtasbi, Khodayar; Parker, Erica M.; Lin, Harrison W.; Djalilian, Hamid R.
Objectives: To evaluate the efficacy of a multi-modal migraine prophylaxis therapy for patients with hyperacusis. Methods: In a prospective cohort, patients with hyperacusis were treated with a multi-modal step-wise migraine prophylactic regimen (nortriptyline, verapamil, topiramate, or a combination thereof) as well as lifestyle and dietary modifications. Pre- and post-treatment average loudness discomfort level (LDL), hyperacusis discomfort level measured by a visual analogue scale (VAS), and scores on the modified Khalfa questionnaire for severity of hyperacusis were compared. Results: Twenty-two of the 25 patients (88%) reported subjective resolution of their symptoms following treatment. Post-treatment audiograms showed significant improvement in average LDL from 81.3 ± 3.2 dB to 86.4 ± 2.6 dB ( P < .001), indicating increased sound tolerability. The VAS discomfort level also showed significant improvement from a pre-treatment average of 7.7 ± 1.1 to 3.7 ± 1.6 post-treatment ( P < .001). There was also significant improvement in the average total score on modified Khalfa questionnaire (32.2 ± 3.6 vs 22.0 ± 5.7, P < .001). Conclusions: The majority of patients with hyperacusis demonstrated symptomatic improvement from migraine prophylaxis therapy, as indicated by self-reported and audiometric measures. Our findings indicate that, for some patients, hyperacusis may share a pathophysiologic basis with migraine disorder and may be successfully managed with multimodal migraine prophylaxis therapy.